Towards manageable magnetic field retrieval in bulk materials - Leeb, H.; Szeywerth, R.; Jericha, E.; Badurek, G. (Physica. B, Condensed matter, 2005)
We present an extension to a recently introduced method for the tomographic investigation of magnetic domain structures in ferromagnetic solids which is based on a combination of neutron interferometry and neutron depolarization concepts. Methodical development of the reconstruction algorithm yields significant improvement compared to previous versions. This is expressed by fast convergence and by doubling the maximum computable pixel size from 1.7 μ m before to at least 4 μ m , which is an important step towards actual experimental realization of this novel tomographic method. Furthermore, it is demonstrated that our algorithm converges even when, as in a real experiment, the measured values of the observables are subject to statistical fluctuations.